The effect of Kinesio (R) taping on pain, functionality, mobility and endurance in the treatment of chronic low back pain: A randomized controlled study - (:unkn) unknown (IOS PRESS, 2017)
BACKGROUND: Low back pain is one of the most important causes of morbidity. OBJECTIVE: This study was designed to evaluate the effect of Kinesio (R) taping on pain, functionality, mobility and endurance in chronic low back pain treatment. METHODS: Patients with chronic low back pain were randomly divided into three groups. Therapeutic ultrasound, hot packs, and transcutaneous electrical nerve stimulation were applied to each group for ten sessions during two weeks, and therapeutic exercises were applied in the clinic under physiotherapist supervision starting from the sixth session. Kinesio (R) tape was applied to the patients in the first group after each treatment session, and placebo tape was applied to the patients in the second group. No taping was applied to the third group, which constituted the control group. All the patients were evaluated pre and post-treatment in respect of pain, functional status (Oswestry scale), flexibility and endurance. RESULTS: The study included 60 patients (32 females). When the initial demographic and clinical characteristics of the groups were evaluated, all assessment results, except the Oswestry scores, were similar (p = 0.000). When the average changes in the clinical evaluations were evaluated after the treatment, a statistically significant improvement demonstrating the superiority of the taping group was observed in pain, functionality, flexibility and endurance values (p = 0.000, 0.000, 0.000, 0.000). CONCLUSIONS: Kinesio (R) taping in chronic low back pain is an easy and effective method which increases the effectiveness of the treatment significantly in a short period when applied in addition to exercise and electrotherapy methods.
Keywords: Back pain; Kinesio (R) taping; physiotherapy; DISABILITY; TRIAL; PREVALENCE